Influence of vermi-fortification on chickpea (Cicer arietinum L.) growth and photosynthetic pigments - Anoop Yadav; V. K. Garg (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The aim of this study was to investigate the effect of different vermicomposts and their dosages on chickpea (Cicer arietinum L.) plants in pot culture experiment. Methods A total of five potting media were prepared containing soil and vermicompost. Soil fortified with 10 and 20 % vermicompost was used as potting media. The fertility status of soil and vermicomposts was quantified. In these potting media, growth, yield and biochemical parameters of chickpea plants were studied up to 90 days. Results The results showed that the fortification of soil with vermicompost significantly stimulated the chickpea plant growth. The plant height, plant shoot biomass, number of pods and photosynthetic pigments were significantly higher in vermicompost-fortified experiments, whereas vermicompost fortification had no significant effect on chickpea seed germination as it was &100 % in all experiments. Total chlorophyll content in chickpea leaves was in the range of 0.437â1.07 mg/g. Similarly, carotenoid content was minimum in control and maximum in 20 % vermicompost containing potting media. Conclusion It was concluded that if soil is fortified with appropriate quantities of vermicompost, the chickpea production per unit area could be enhanced significantly